Teaching microbial analysis techniques for the characterisation of baker's yeast through the inquiry-based laboratory - Muhammad Saefi; Widi Cahya Adi; Amining Rahmasiwi; Hidayati Maghfiroh; M. Eval Setiawan; Miza Nina Adlini; Syarif Rizalia (University of Muhammadiyah Malang, 2023)
Laboratory course activities often focus on